Molecular docking of polyether ether ketone and nano-hydroxyapatite as biomaterial candidates for orthodontic mini-implant fabrication. - I Gusti Aju Wahju Ardani; Alexander Patera Nugraha; Monika Nilam Suryani; Ryan Hafidz Putra Pamungkas; Devani Githa Vitamamy; Rizky Alif Susanto; Riyanarto Sarno; Aziz Fajar; Viol Dhea Kharisma; Albertus Putera Nugraha; Tengku Natasha Eleena binti Tengku Ahmad Noor (GarVal Editorial Ltda., 2022)
Context: Modified polyether ether ketone (PEEK) by adding nano-hydroxyapatite (HA) material on its fixture for mini-implant fabrication may increase resistance force through osseointegration. Aims: To analyze the binding molecular docking of PEEK incorporated with HA as a biomaterial candidate for orthodontic mini-implant fabrication through a bioinformatic approach, an in silico study. Methods: 3D ligand structure consisting of HA, PEEK and target proteins consisting of osteopontin, osteocalcin, osteonectin, bone morphogenetic protein 4 (BMP4), bone morphogenetic protein 2 (BMP2), bone morphogenetic protein 7 (BMP7), alkaline phosphatase (ALP), runt-related transcription factor 2 (RUNX2), Insulin growth factor-1 (IGF-1), osterix, tartrate-resistant acid phosphatase (TRAP), collagen alpha-1 (COL1A1) obtained from RCSB-PDB. It was analyzed the binding affinity of a single HA, PEEK, and HA + PEEK complex to twelve target proteins related to osseointegration. The types of chemical interactions produced by the ligands in the target protein domain consisted of Van der Waals, hydrogen, hydrophobic, pi, and alkyl. Results: The blind docking simulation succeeded in identifying the most negative binding affinity; it was found in the HA + PEEK molecular complex compared to HA and PEEK in the single condition. The type of chemical interaction formed consisted of hydrogen, van der Waals, pi, and alkyl. HA+PEEK showed the most negative binding affinity with ALP and IGF-1, as much as -8.7 binding affinity. Conclusions: The molecular docking of PEEK with HA exhibited a prominent binding affinity with osteogenic markers like ALP and IGF-1 in silico, allowing it to have a higher potential than nano-HA or PEEK as a single biomaterial for osseointegration as the fabrication of mini-implants that may support orthodontic treatment.